A disposable and flexible graphene electrode fabricated by inkjet printing of an aqueous surfactant-free graphene oxide dispersion - Chamari Pothipor (2018)
© 2015 The Chemical Society of Japan. Herein, the fabrication of a simple, low-cost, disposable, and flexible graphene (GP) electrochemical electrode by inkjet printingof the aqueous graphene oxide (GPO) dispersion ink was investigated. In terms of conductivity enhancement, the inkjetprinted GPO chip was chemically reduced, and exhibited high electrochemical response, reactivity, and stability. The electrode is a promising candidate for electrochemical applications.